Linking Personality Traits To Job Satisfaction In Teachers Of Private Universities, Pakistan: Psychological Empowerment As A Mediator - Shah, Dr. Muhammad Anees ul Husnain; Danish, Dr Muhammad; Siddiqui, Dr. Mahreen; Ali, Dr. Nazim; Hussain, Dr. Altaf; Jan, Muhammad Farooq (Migration Letters, 2024)
The main objective of this study was to investigate the influence of personality traits on both job satisfaction (JS) and psychological empowerment (PE). This study also aims at testing the mediating effect of PE in the relationship between personality traits (PTs) and JS. In order to accomplish these goals, this study employed a quantitative approach for analysis. The target population of this study consisted of personnel working at public sector universities in Balochistan and Khyber Pakhtunkhwa. The adoption of a random sampling approach occurred. The study employed close-ended questions. 600 questionnaires were distributed to the faculty members. A total of 492 respondents, accounting for 82% of the sample, completed the questionnaires. Results indicate a Pearson correlation value (r=0.583, p=0.000) between PTs and JS, demonstrating a statistically significant positive link. The correlation coefficient (r=0.538, p= 0.000) between PTs and PE indicates a highly significant and favourable association. The correlation analysis also reveals a strong positive association between PE and JS, with a correlation coefficient (r) of 0.469 and a p-value of 0.000. PE was also found to have a partial mediating role in the relationship between PTs and JS.